A Study of the Influence of Online Information on the Changes in the Warsaw Stock Exchange Indexes - Młodzianowski, Piotr (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
The article presents the results of a study on the influence of online information originating from financial websites on changes in the Warsaw Stock Exchange indexes. The first part is theoretical. It describes the issue of text mining and sentiment analysis and their use in the text analysis process. The next part of the article describes the characteristics of the study. A selection was made of Polish financial websites that may trigger reactions from investors on the Warsaw Stock Exchange. Words occurring on the analysed websites were selected and put into classes. Then the relation between changes in WSE indexes and the frequency of appearance of individual words within the classes was analysed. The last part of the article presents the study results, discusses the possibilities of using them and indicates further areas for research.